Efeitos do beta-cariofileno nas alterações comportamentais. Bioquímicas e na motilidade gastrintestinal de ratos submetidos ao modelo de doença de Parkinson induzida por 6-OHDA: avaliação do eixo cérebro-intestino - Gomes, Francisco José (2021)
Parkinson’s disease (PD) is a neurodegenerative disorder associated with tremor, rigidity, dementia, and gastrointestinal symptoms (eg, constipation, dysphagia, nausea, vomiting). These signs and symptoms relate to the dopaminergic neuronal death of the substantia nigra pars compacta in the central nervous system, which causes characteristic movement disorders and vagus nerve dysfunction. Although there are available treatments for PD, they are restricted to symptom relief and have no effects on lesion recovery or disease progression. Researches indicate the use of plant-derived compounds as a promising alternative on this subject. The beta-caryophyllene (BCP), an important cannabinoid derived from essential oils of different species, has demonstrated pharmacological properties in different types of cells and tissues. However, its effects on PD have not been properly demonstrated. This study aims to analyse the BCP effects on the 6-OHDA-induced PD model in rats, by addressing alterations of gastrointestinal motility. Male Wistar rats (250-300g) underwent unilateral intrastriatal injection of 6-OHDA (21 µg) in the experimental groups or 0.9% saline (6µl/rat) in the Sham group. One hour after surgery, the rats received BCP (15, 50, and 100 mg/kg) or 0.9% saline via oral gavage for 21 days. On the 14th day of treatment, the rats underwent behavioural tests (open field, apomorphine, and rotarod). Finally, 24 hours after the final administration of BCP or 0.9% saline, the rats were sacrificed in order to perform gastric emptying and brain areas removal (hippocampus, prefrontal cortex, and striatum) for neurochemical assays (lipid peroxidation, reduced glutathione, and nitrite/nitrate determination). In the open field test, 6-OHDA reduced the number of crossings and raised the time of immobility; the administration of BCP, mainly at 15 mg/kg, reduced some of these effects, when compared to the Sham group. In the apomorphine-induced rotation test, 6- OHDA raised the number of contralateral rotations, when compared to the Sham group; the administration of BCP at all doses reversed this effect. In the rotarod test, 6-OHDA reduced the latency time to fall and duration of permanence in the revolving bar; the administration of BCP only at the lowest dose (15 mg/kg) reversed this effect significantly. In all tested brain areas, 6-OHDA raised the lipid peroxidation/oxidative stress and diminished the reduced glutathione levels; the administration of BCP, mainly at low doses, reversed these effects. The central nervous system alterations reverberated in the gastrointestinal tract of the injured rats, in which a raise of transit time occurred; the administration of BCP at 15 and 50 mg/kg reversed this effect. These gastrointestinal alterations may be associated with the rise of oxidative stress locally; the administration of BCP also reduced these parameters, especially lipid peroxidation. A rise of studies are of utmost importance for more consistent results, though BCP appears to be effective in reducing motor disorders which were induced by the neurotoxin 6-OHDA. The BCP is a promising factor in the search for new pharmacological treatments for PD.